Hubungan Tingkat Pengetahuan Ibu Tentang Pneumonia dengan Kejadian Pneumonia pada Balita - Mayaswari, Kadek Githa; Sipahutar, Ida Erni; Cakra, NLP Yunianti Suntari (Jurnal Gema Keperawatan, 2024)
Pneumonia is one of the diseases most often experienced by toddlers. There are several factors that cause a child under five to experience pneumonia, namely the first is the characteristics of the mother which consists of the mother's education, the mother's knowledge about pneumonia, the mother's occupation, then the second factor in children under five which consists of exclusive breastfeeding, the immunization status of the child under five, the nutritional status of the child under five. , and finally environmental factors consisting of residential density, indoor air pollution, distance to health facilities. The aim of this study was to determine the relationship between the mother's level of knowledge about pneumonia and the incidence of pneumonia in toddlers. The type of research used in this research is non-experimental quantitative research. The sampling technique used was a purposive sampling technique with a total of 31 samples taken. Data analysis used the chi square test to determine the relationship between the independent variable, namely the level of knowledge, and the dependent variable, the incidence of pneumonia. The instrument used in this research was a questionnaire. The research was conducted at the Mangusada Badung Regional Hospital (RSD). The results of statistical tests showed that there was a relationship between the level of knowledge and the incidence of pneumonia, with a p value of 0,047. Advice for mothers who have toddlers is to increase their knowledge about pneumonia so that they can increase their ability to prevent their children from experiencing pneumonia.